Understanding multi‐stakeholder needs, preferences and expectations to define effective practices and processes of patient engagement in medicine development: A mixed‐methods study. (17th February 2021) - Faulkner, Stuart D; Sayuri Ii, Suzanne; Pakarinen, Chi; Somers, Fabian; Jose Vicente Edo, Maria; Prieto Remon, Lucia; Diaz Ponce, Ana; Gove, Dianne; Ferrer, Elisa; Nafria, Begonya; Bertelsen, Neil; Boudes, Mathieu; et al.
Abstract: Background: The holistic evolution of patient engagement in medicines development requires a more detailed understanding of the needs of all involved stakeholders, and one that better accounts for the specific needs of some potentially vulnerable patient populations and key stages in medicines development. Objective: The purpose of this convergent mixed‐methods study was to better understand the needs of different stakeholders concerning patient engagement at three key stages in medicines development: research priority setting, clinical trial design and early dialogues with Health Technology Assessment bodies and regulators. Design: This study brought together findings from three sources: i) an online questionnaire, ii) face‐to‐face consultations with two potentially vulnerable patient populations, a workshop with Health Technology Assessment bodies, and iii) three‐step modified Delphi methodology. Results: Overall stakeholders still need additional varied support mechanisms to undertake, sustain or measure value of patient engagement. Health Technology Assessment bodies need better rationale for patient engagement in early dialogue and tools to support its implementation. Improved awareness and understanding of the need and value that involving patients, who are often considered as potentially vulnerable, can bring is needed, as is better accommodation of their specific needs. Similarly, weighted Delphi categories were as follows: aims and objectives, and sustainability. Several additional themes were common across the three key stages in medicines development. Conclusion: This broad‐reaching study provides the blocks needed to build a framework for patient engagement in medicines development. Patient or Public Contribution: Patients were involved in review and interpretation of data.